2006
DOI: 10.1124/mol.106.024711
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Studies of Multiple Binding Sites on M4 Muscarinic Acetylcholine Receptors

Abstract: This study investigated the reciprocal cross-interactions between two distinct allosteric sites on the M 4 muscarinic acetylcholine receptor (mAChR) in the absence or presence of different orthosteric ligands. Initial studies revealed that two novel benzimidazole allosteric modulators, 17-␤-hydroxy-17-␣-ethy nyl-delta(4)-androstano [3,2-b] (McN-A-343), or xanomeline] revealed low degrees of negative cooperativity between WIN 62,577 and each agonist, whereas stronger negative cooperativity was observed against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…This finding is in general agreement with our prior mutagenesis study (Chan et al, 2008), which suggested an engagement of the modulator with extracellular loop regions of the M 4 mAChR and an important function of D 432 in the third extracellular loop; this residue has been implicated in the binding of the prototypical modulator, gallamine, to the M 4 mAChR (Gnagey et al, 1999). In contrast, the interaction between LY2033298 and atropine was negatively cooperative, whereas that between LY2033298 and WIN51708 was neutrally cooperative; both findings clearly indicate that LY2033298 does not interact with either the orthosteric site or a second allosteric site on the M 4 mAChR recognized by staurosporine, KT5720, and various WIN compounds (Lanzafame et al, 2006;Lazareno et al, 2000Lazareno et al, , 2002.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This finding is in general agreement with our prior mutagenesis study (Chan et al, 2008), which suggested an engagement of the modulator with extracellular loop regions of the M 4 mAChR and an important function of D 432 in the third extracellular loop; this residue has been implicated in the binding of the prototypical modulator, gallamine, to the M 4 mAChR (Gnagey et al, 1999). In contrast, the interaction between LY2033298 and atropine was negatively cooperative, whereas that between LY2033298 and WIN51708 was neutrally cooperative; both findings clearly indicate that LY2033298 does not interact with either the orthosteric site or a second allosteric site on the M 4 mAChR recognized by staurosporine, KT5720, and various WIN compounds (Lanzafame et al, 2006;Lazareno et al, 2000Lazareno et al, , 2002.…”
Section: Discussionmentioning
confidence: 55%
“…Preliminary mutagenesis experiments with LY2033298 also implicated extracellular loop regions in the actions of the modulator (Chan et al, 2008). However, there is another class of 'atypical' modulators, such as WIN51708, WIN62577, staurosporine, and KT5720, that bind to a second, currently unresolved, allosteric site on mAChRs (Lanzafame et al, 2006;Lazareno et al, 2000Lazareno et al, , 2002. Thus, to gain more definitive insight into which allosteric site is involved in the binding of LY2033298, we exploited the ability of the modulator to also act as an agonist and performed functional interaction studies between this compound and either the classic orthosteric antagonist, atropine, the 'prototypical-site' allosteric modulator, C 7 /3-phth, or the 'second-site' allosteric modulator, WIN51708.…”
Section: Ly2033298 Potentiates Both the Affinity And The Efficacy Of mentioning
confidence: 99%
“…It differs from a recent ab initio modeling prediction (Peng et al, 2006). Dissimilar docking of NMS and QNB might affect not only the kinetics of formation and breakdown but also the functional properties of the receptor-ligand complexes, perhaps accounting for differences in cooperativity between NMS, QNB, and allosteric ligands (Lanzafame et al, 2006) and affecting the potential for inverse agonism (Schwartz et al, 2006). The shorter side chain of ACh also fails to penetrate far into the TM domain and is unlikely to interact strongly with TM5 in the ground state of the receptor.…”
Section: Discussionmentioning
confidence: 95%
“…Radioligand binding with the muscarinic receptor ligand [ 3 H]QNB (specific activity, 37 Ci/mmol; PerkinElmer Life and Analytical Sciences, Waltham, MA) was performed as described previously using membranes from the human detrusor muscle and mucosa (Mansfield et al, 2005) and from CHO cells (Lanzafame et al, 2006).…”
Section: Methodsmentioning
confidence: 99%